Volume 4: Fluid-Structure Interaction 2011
DOI: 10.1115/pvp2011-57102
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Excitation Forces in a Normal Triangular Tube Bundle Subjected to Two-Phase Cross Flow

Abstract: This paper presents test results of vibration forces in a normal triangular tube bundle subjected to air-water cross-flow. The dynamic lift and drag forces were measured with strain gage instrumented cylinders. The array has a pitch-to-diameter ratio of 1.5, and the tube diameter is 38 mm. A wide range of void fraction and fluid velocities were tested. The experiments revealed significant forces in both the drag and lift directions. Constant frequency and quasi-periodic fluid forces were found in addition to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 0 publications
1
15
4
Order By: Relevance
“…Conversely, only few experimental data for turbulence-induced vibration mechanism under conditions twophase flow are available, which is somehow surprising since this vibration mechanism is unavoidable, and is always present in heat exchanger tube bundles. Actually, more recent experimental studies (ZHANG et al, 2007;PERROT et al, 2011) have shown that there is a lack of knowledge in this mechanism since they found out that it consists of turbulence and periodic components, which have not been reported in literature before.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, only few experimental data for turbulence-induced vibration mechanism under conditions twophase flow are available, which is somehow surprising since this vibration mechanism is unavoidable, and is always present in heat exchanger tube bundles. Actually, more recent experimental studies (ZHANG et al, 2007;PERROT et al, 2011) have shown that there is a lack of knowledge in this mechanism since they found out that it consists of turbulence and periodic components, which have not been reported in literature before.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these mechanisms related to quasi-periodic forces are currently been studied and information about its causes is scarce. Anyway, it is worth pointing out that Zhang et al (2007) and Perrot et al (2011) found these mechanisms with quasi-periodic forces by analyzing the buffeting vibration induced by two-phase flow.…”
Section: Introduction To Flow-induced Vibration Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations